Expanded cardiovascular phenotype of Myhre syndrome includes tetralogy of Fallot suggesting a role for SMAD4 in human neural crest defects. Issue 5 (13th January 2022) - Cappuccio, Gerarda; Brunetti‐Pierri, Nicola; Clift, Paul; Learn, Christopher; Dykes, John C.; Mercer, Catherine L.; Callewaert, Bert; Meerschaut, Ilse; Spinelli, Alessandro Mauro; Bruno, Irene; Gillespie, Matthew J.; Dorfman, Aaron T.; et al.
Abstract: Tetralogy of Fallot (ToF) can be associated with a wide range of extracardiac anomalies, with an underlying etiology identified in approximately 10% of cases. Individuals affected with Myhre syndrome due to recurrent SMAD4 mutations frequently have cardiovascular anomalies, including congenital heart defects. In addition to two patients in the literature with ToF, we describe five additional individuals with Myhre syndrome and classic ToF, ToF with pulmonary atresia and multiple aorto‐pulmonary collaterals, and ToF with absent pulmonary valve. Aorta hypoplasia was documented in one patient and suspected in another two. In half of these individuals, postoperative cardiac dysfunction was thought to be more severe than classic postoperative ToF repair. There may be an increase in right ventricular pressure, and right ventricular dysfunction due to free pulmonic regurgitation. Noncardiac developmental abnormalities in our series and the literature, including corectopia, heterochromia iridis, and congenital miosis suggest an underlying defect of neural crest cell migration in Myhre syndrome. We advise clinicians that Myhre syndrome should be considered in the genetic evaluation of a child with ToF, short stature, unusual facial features, and developmental delay, as these children may be at risk for increased postoperative morbidity. Additional research is needed to investigate the hypothesis that postoperative hemodynamics in these patients may be consistent with restrictive myocardial physiology.